Why Smoggy Days Suppress Our Mood: Automatic Association Between Clarity and Valence - Liu, Yiguang; Yin, Jun; Liang, Junying (Frontiers in Psychology, 2019)
The intuition of clarity-valence association seems to be pervasive in daily life, however, whether there exists a potential association between clarity (i.e., operationalized as visual resolution) and affect in human cognition remains unknown. The present study conducted five experiments, and demonstrated the clarity-valence congruency effect, that is, the evaluations showed performance advantage in the congruent conditions (clear-positive, blurry-negative). Experiment 1 through 3 demonstrated the influence of the perception of clarity on the conceptualization of affective valence, while Experiment 4 & 5 verified the absence of the influence of conceptualization on perception, thus the unidirectionality of clarity-valence association in cognition is confirmed. The findings extend the affective perceptual-conceptual associations into the dimension of clarity, thus providing support for the ideas of embodied cognition as well as implications for our preference for clarity and aversion to blur.